Integrals Of Differance: A Derridean Critique Of The Selected Poems Of Ondaatje (Journal of Namibian Studies : History Politics Culture, 2023)
In the 1980s, postmodernism emerged as an academic area in literature, film, art, and other fields. It is a contradictory and dismantling phenomenon. Derrida's différance is a trait of postmodernism, but Ondaatje's poetry has not yet been used to investigate its integrals, "to differ" and "to defer." The study makes the case that Ondaatje's selected poems reflect integrals of différance since these integrals can be clearly observed in his poetry's theme and textual techniques, which rank him among other postmodern poets. The study investigated: i. how the first integral of différance, which is "to differ," is reflected in the study's eleven poems. ii. examining "to differ" or dissolving the boundaries between postmodernist textual techniques, such as intertextuality, non-linear structure, parody, pastiche, and multi-voiced narrative in Ondaatje's poems iii. And how these poems reflect the second component of différance, "to defer," postponement or open-endedness. In this qualitative study, these integrals have been investigated through textual analysis from the perspective of différance. This study explores how Ondaatje’s poetry reflects ‘to differ’ through blurring the boundaries between man and nature, present and primitivism, prose and poetry, husband, and wife, east (Ceylon) and U.S. (Connecticut) and through ‘to defer’/ postponement, open-endedness has been identified in Ondaatje’s poetry in the form of rejection of authorial voice and heterodiegetic narrative.